Preliminary Evidence that Melatonin Is not a Biomarker in Children and Adolescents With Episodic Migraine. Issue 7 (3rd May 2019) - Berger, Anthony; Litwin, Jessica; Allen, Isabel Elaine; Qubty, William; Irwin, Samantha; Waung, Maggie; Gelfand, Amy A.
Abstract : Background: To date, there have not been reliable biomarkers to identify impending migraine episodes. A prior study in adults with migraine demonstrated a reduction in the urinary metabolic substrate of melatonin (urinary 6‐sulfatoxymelatonin; aMT6s) during a migraine. The aim of this study was to examine whether evening urinary melatonin metabolite levels could predict migraine the next day in children and adolescents with migraine. Methods: Twenty‐one children and adolescents with migraine (aged 5‐17 years) were recruited to this observational study conducted at UC San Francisco to provide urine samples for 10 days and maintain a prospective headache diary during the same period. Nightly melatonin metabolite 6‐sulfatoxymelatonin in urine was assayed and results from nights preceding migraine were compared to nights preceding a non‐headache day. Results: Mean (±SD) aMT6s levels the night prior to a migraine attack were 56.2 ± 39.0 vs 55.4 ± 46.6 ng/mL ( P = .915), and mean melatonin metabolite levels the night following migraine were 55.5 ± 46.9 vs 57.0 ± 37.7 ng/mL ( P = .841). However, in post hoc exploratory analyses, aMT6s levels were lower the night before a migraine in those who experienced aura or premonitory symptoms. Conclusion: While urinary melatonin metabolites do not predict migraine attacks in children and adolescents overall, they may be predictive in those who experience premonitory phase symptoms as part of their migraine attacks.